214 Generation of Isogenic Cell Lines to Study a Single Disease Associated Variant at the 1P13 Cad Risk Locus. (31st May 2014) - McVey, David; Samani, Nilesh; Webb, Tom
Abstract : Coronary artery disease (CAD) is a leading cause of mortality worldwide and has a significant heritable component. In the last few years genome-wide association studies (GWAS) have identified 46 genome-wide significant loci associated with risk of CAD. A major post-GWAS challenge is the functional investigation of the biological and cellular mechanisms by which specific variants at CAD associated loci contribute to disease. The functional impact of putative functional variants is likely to be relatively subtle and could be masked by other genetic variation. We have therefore established genome editing techniques to create precise knock-in of single nucleotides in disease-relevant human cell lines, allowing the effects of a CAD associated variant of interest to be investigated on an isogenic genetic background. Here, we present a proof-of-principal investigation of a CAD associated locus using isogenic human cell lines created using genome editing. Musunuru et al (Nature. 2010. vol 466 (7307). pp. 714–9) presented compelling evidence that rs12740374 is the causal variant at the 1p13 CAD locus. They show that the risk allele of rs12740374 disrupts the binding of the transcription factor CEBPα and consequently alters the cis transcriptionalregulation of CELSR2, PSRC1 and SORT1 and identify the SORT1 protein as a novel mediator of LDL cholesterol metabolism. We have used recombinant adeno-associated virus (rAAV)-mediated genome editing to knock-in the non-risk allele of rs12740374 in the HepG2 (hepatic carcinoma) cell line. Using qPCR we show that rs12740374 genotype affects the expression of nearby genes, including SORT1. Further functional studies of the 1p13 locus using these isogenic cell lines are ongoing. Our data shows that genome editing is a powerful functional genomics tool in the investigation of specific CAD-associated variants.